Attosecond probe of valence electron wavepackets by sub-cycle sculpted laser fields - Xie, Xinhua (2012)
We experimentally and theoretically demonstrate a self-referenced wave-function retrieval of a valence-electron wave packet during its creation by strong-field ionization with a sculpted laser field. Key is the control over interferences arising at different time scales. Our work shows that the measurement of subcycle electron wave-packet interference patterns can serve as a tool to retrieve the structure and dynamics of the valence-electron cloud in atoms on a sub-10-as time scale.